Detecting treeline dynamics in response to climate warming using forest stand maps and Landsat data in a temperate forest - Arekhi, Maliheh; Yesil, Ahmet; Ozkan, Ulas Yunus; Sanli, Fusun Balik (SPRINGER HEIDELBERG, 2018)
Background: Treeline dynamics have inevitable impacts on the forest treeline structure and composition. The present research sought to estimate treeline movement and structural shifts in response to recent warming in Cehennemdere, Turkey. After implementing an atmospheric correction, the geo-shifting of images was performed to match images together for a per pixel trend analysis. We developed a new approach based on the NDVI, LST (land surface temperature) data, air temperature data, and forest stand maps for a 43-year period. The forest treeline border was mapped on the forest stand maps for 1970, 1992, 2002, and 2013 to identify shifts in the treeline altitudes, and then profile statistics were calculated for each period. Twenty sample plots (10 x 10 pixels) were selected to estimate the NDVI and LST shifts across the forest timberline using per-pixel trend analysis and non-parametric Spearman's correlation analysis. In addition, the spatial and temporal shifts in treeline tree species were computed within the selected plots for four time periods on the forest stand maps to determine the pioneer tree species. Results: A statistically significant increasing trend in all climate variables was observed, with the highest slope in the monthly average mean July temperature (tau = 0.62, rho < 0.00). The resultant forest stand maps showed a geographical expansion of the treeline in both the highest altitudes (22 m-45 m) and the lowest altitudes (20 m-105 m) from 1970 to 2013. The per pixel trend analysis indicated an increasing trend in the NDVI and LST values within the selected plots. Moreover, increases in the LST were highly correlated with increases in the NDVI between 1984 and 2017 (r = 0.75, rho < 0.05). Cedrus libani and Juniperus communis spp. were two pioneer tree species that expanded and grew consistently on open lands, primarily on rocks and soil-covered areas, from 1970 to 2013. Conclusion: The present study illustrated that forest treeline dynamics and treeline structural changes can be detected using two data sources. Additionally, the results will have a significant contribution to and implication for treeline movement studies and forest landscape change investigations attempting to project climate change impacts on tree species in response to climate warming. The results will assist forest managers in establishing some developmental adaptation strategies for forest treeline ecotones.
Keywords: NDVI; Geoshift; LST; Timberline; Mann-Kendall; Landsat; Climate warming; LINE DYNAMICS; TIBETAN PLATEAU; MOUNTAIN PLANTS; VEGETATION; LANDSCAPE; PATTERNS; DRIVERS; IMAGERY; TRENDS; VARIABILITY; Forestry